The Making of TEBU (Tebak Budaya) Game in Preserving Indonesian Cultural Characteristics - Anjar Sundaru; Maria Bella Ismiarti (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2020)
Technology has developed very quickly along with human’s need to facility that helps them finish their work. Regarding the situation, combining technology advancement with history and culture brings in advantages like easing and accelerating information access and broadening knowledge concerning Indonesian history and culture through computer flowchart. In this study, the authors emphasize Indonesian cultural characteristics in terms of traditional housing, dances, and songs. This study aims to create a learning medium for all people, so they know Indonesian history and culture better.